2021
DOI: 10.3390/biom11121899
|View full text |Cite
|
Sign up to set email alerts
|

H2S Donors and Their Use in Medicinal Chemistry

Abstract: Hydrogen sulfide (H2S) is a ubiquitous gaseous signaling molecule that has an important role in many physiological and pathological processes in mammalian tissues, with the same importance as two others endogenous gasotransmitters such as NO (nitric oxide) and CO (carbon monoxide). Endogenous H2S is involved in a broad gamut of processes in mammalian tissues including inflammation, vascular tone, hypertension, gastric mucosal integrity, neuromodulation, and defense mechanisms against viral infections as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 259 publications
(321 reference statements)
1
19
0
3
Order By: Relevance
“…To further explore the roles of CTH/H 2 S in the inflammation process, β-cyano- l -Alanine (BCA), a CTH-specific reversible inhibitor [ 21 , 22 ], and NaHS, a H 2 S donor to trigger H 2 S release in cells [ 23 ], were introduced to uncover the CTH/H 2 S function. CTH and CBS expression was evaluated by qRT-PCR and WB assays.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the roles of CTH/H 2 S in the inflammation process, β-cyano- l -Alanine (BCA), a CTH-specific reversible inhibitor [ 21 , 22 ], and NaHS, a H 2 S donor to trigger H 2 S release in cells [ 23 ], were introduced to uncover the CTH/H 2 S function. CTH and CBS expression was evaluated by qRT-PCR and WB assays.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that some OSCs could exert their anti-inflammatory effect through the inhibition of the MAPK and NF-κB pathways, but their detailed mechanisms are still unclear ( Rodrigues and Percival, 2019 ). A large amount of literature has indicated that the benefits of OSCs are associated with the number of sulfur atoms in their structure, which is closely related to its potential to increase endogenous hydrogen sulfide (H 2 S) ( Benavides et al, 2007 ; Magli et al, 2021 ). H 2 S has been shown to play an important regulatory role in the inflammatory processes and inhibit the activation of NF-κB and MAPKs ( Stuhlmeier et al, 2009 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there was a significant decrease of lipid and protein oxidation products and a substantial increment in the total antioxidant capacity and total thiol levels in the plasma samples from the study group as compared to the control group [ 47 ]. Some recent reviews of available H 2 S donors that serve as a platform for the release of H 2 S have underlined their considerable promise as favorable drugs in the clinical treatment of many diseases [ 48 , 49 , 50 ]. However, a series of experiment on numerous types of animals, including lamprey, trout, mouse, rat, pig, and cow, reported an essentially undetectable basal level of H 2 S gas (<100 nM total sulfide) in blood in all animals.…”
Section: Antioxidant Activities: a Conventional Anti-aging Paradigm O...mentioning
confidence: 99%